Fully atomistic modeling of plasmonic bimetallic nanoparticles: nanoalloys and core-shell systems - Nicoli, Luca; Lafiosca, Piero; Grobas Illobre, Pablo; Bonatti, Luca; Giovannini, Tommaso; Cappelli, Chiara (Frontiers in Photonics, 2023)
The recently developed ωFQFμ model (ACS Photonics, 9, 3,025–3,034) is extended to bimetallic nanoparticles, such as nanoalloys and core-shell systems. The method finds its grounds in basic physical concepts, such as Drude conduction theory, electrostatics, interband transitions, and quantum tunneling. The approach, which is parametrized on ab initio simulations of Ag-Au nanoalloys, is challenged against complex Ag-Au nanostructures (spheres, nanorods, and core-shell nanoparticles). Remarkable agreement with available experimental data is found, thus demonstrating the reliability of the newly developed approach.